Pengaruh Metode Active Learning Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Fikih MTs Al Mizan - Fhitria, Shoelicha; Lisnawati, Santi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the effect of student learning motivation between students who use Active Learning learning methods and students who use conventional learning methods. This research uses a quasi-experimental quantitative research method. The population used in this research as subjects were all class VIII students at Mts AL MIZAN, Cibinong District, Bogor Regency and took a sample of 80 students from class VIII A as the experimental class totaling 40 students and class VIII B as the experimental class. control class consisting of 40 students. The collection technique is carried out through tests using a questionnaire as a measuring tool. The average pretest score for the control class was 65.91 and the experimental class was 67.12, while the average posttest score for the control class was 75.42 and the experimental class was 84.10. The t-test results of 0.000 < 0.05 indicate that there is a significant difference in increasing motivation to learn Islamic jurisprudence between the control class and the experimental class.